A non-local 3D lattice particle framework for elastic solids. (1st March 2016) - Chen, Hailong; Liu, Yongming
Abstract: A novel non-local lattice particle method for three-dimensional elasticity and fracture simulation of isotropic solids is proposed in this paper. First, the basic concept and detailed derivation of the proposed model are given. Three cubic lattice packing are investigated using the proposed model and simulation results are compared with classical finite element method solutions. The performance of these lattice structures are assessed using several benchmarks, for both deformation and brittle fracture problems. From the simulation results, good agreements with both analytical solution and experimental data are observed. Conclusions and future work are drawn based on this study.